Visual Analysis of the Finite‐Time Lyapunov Exponent. (18th July 2020) - Sagristà, Antoni; Jordan, Stefan; Sadlo, Filip
Abstract: In this paper, we present an integrated visual analytics approach to support the parametrization and exploration of flow visualization based on the finite‐time Lyapunov exponent. Such visualization of time‐dependent flow faces various challenges, including the choice of appropriate advection times, temporal regions of interest, and spatial resolution. Our approach eases these challenges by providing the user with context by means of parametric aggregations, with support and guidance for a more directed exploration, and with a set of derived measures for better qualitative assessment. We demonstrate the utility of our approach with examples from computation fluid dynamics and time‐dependent dynamical systems.